Emergence of New Predictors Projecting the Definite Article Variability: Evidence from Nigerian English - Mayowa Akinlotan (Baltic Journal of English Language, Literature and Culture)
An important syntactic system in the noun phrase (NP) is the definite article system. The definite article system in emerging varieties of English, such as Nigerian and Indian, have been shown to manifest varying degrees of variability in their usages, given different contexts (Platt, Weber and Ho, 1984; Wahid, 2013; Akinlotan, 2016b; Akinlotan 2017). In addition to the fact that little has been done in quantifying this phenomenon, too little number of predictors explicating the scenarios where we might find certain definite article usages in different but specific contexts in emerging varieties has also been put forward. Following Wahid (2013), a revision of Hawkins’s (1978) theoretical framework for the definite article usages, together with test statistic, the present study investigated 19276 tokens of the, spread across seven text types of academic, media, learner, interactional, popular, literary, and administrative. The study which Akinlotan expands (2017) shows that previously untested predictors of presence/absence of premodification and determiner structure, animacy and class of the head noun, and syntactic function of the NP, account for variability in the definite article usage in our corpus. In fact, these newly tested predictors show stronger influence than a well-known predictor of register (Biber et al., 1999; Wahid, 2013).